Resistance through Re‐presenting Culture: Aboriginal Student Filmmakers and a Participatory Action Research Project on Health and Wellness - Riecken, Ted; Conibear, Frank; Michel, Corrine; Lyall, John; Scott, Tish; Tanaka, Michele; Stewart, Suzanne; Riecken, Janet; Strong‐Wilson, Teresa (Canadian Journal of Education/Revue canadienne de l’éducation, 2006)
This article focuses on a participatory research project designed to promote student use of digital video to explore conceptions of health and wellness. We have viewed aspects of student resistance through the cultural perspectives that guide the Aboriginal education programs involved with the study. In presenting this piece, we have experimented with a number of different styles to represent the different cultural, ethical, and educational dimensions of the research project and to advance a form of resistance to standardized representations of research results. Through video re‐presentation of culture, students resisted the privileging of text and dominant cultural constructions of their personal identities. Key words: digital video, First Nations education, multiple literacies, health education, community and university partnerships Cet article porte sur un projet de recherche collectif visant à promouvoir l’utilisation de la vidéo numérique chez les élèves en vue d’explorer diverses conceptions de la santé et du bien‐être. Les auteurs analysent certains aspects de la résistance des élèves à travers les perspectives culturelles qui orientent les programmes d’enseignement à l’intention des autochtones compris dans l’étude. Dans leur recherche, les auteurs ont fait appel à différents styles de représentation des diverses dimensions culturelles, éthiques et pédagogiques de l’étude et ont promu une forme de résistance aux représentations traditionnelles des résultats de recherche. À travers la re‐présentation vidéo de la culture, les élèves ont refusé d’accorder une place privilégiée au texte et aux constructions culturelles dominantes de leurs identités personnelles. Mots clés : vidéo numérique, enseignement dispensé aux autochtones, littératies multiples, éducation en matière de santé, partenariat entre la communauté et l’université.